Technology Facilitation in the Rural School: An Analysis of Options - Mark Hawkes; Pamela Halverson; Bradley Brockmueller (Journal of Research in Rural Education, 2002)
As a part of their programs for education reform and opportunity, rural schools are applying desktop and telecommunications technology with increasingly frequency. The use of these technologies requires extensive maintenance and training . However, an era of downsizing and buget cuts leaves rural schools inquiring how they can best support the use of educational technologies in their schools. This study attempts to determine a practice-based solution to the rural school technology support question by surveying technology coordinators (n = 129) from the upper plains region of the U.S. Data on job responsabilities, profesional training, training quality, and task proficency is gathered. Analysis shows that heavy pedagogical and technical demands are placed on rural technology coordinators. The study findings strongly suggest that the preparation of the rural technology coordinator include a transition from the classroom, and an advance degree in a relevant program of study that includes network administration, computer hardware characteristics, multimedia production, instructional design, and leadership for school change and growth.